Exploring self-determined solutions to service and system challenges to promote social and emotional wellbeing in Aboriginal and Torres Strait Islander people: a qualitative study - Dawson, Anna P.; Warrior, Eugene; Pearson, Odette; Boyd, Mark A.; Dwyer, Judith; Morey, Kim; Brodie, Tina; Towers, Kurt; Waters, Sonia; Avila, Cynthia; Hammond, Courtney; Lake, Katherine J.; et al. (Frontiers in Public Health, 2023)
Introduction: Many Aboriginal and Torres Strait Islander people living on Kaurna Country in northern Adelaide experience adverse health and social circumstances. The Taingiwilta Pirku Kawantila study sought to understand challenges facing Aboriginal and Torres Strait Islander communities and identify solutions for the health and social service system to promote social and emotional wellbeing.Methods: This qualitative study applied Indigenous methodologies undertaken with Aboriginal and Torres Strait Islander governance and leadership. A respected local Aboriginal person engaged with Aboriginal and Torres Strait Islander community members and service providers through semistructured interviews and yarning circles that explored community needs and challenges, service gaps, access barriers, success stories, proposed strategies to address service and system challenges, and principles and values for service design. A content analysis identified the breadth of challenges in addition to describing key targets to empower and connect communities and optimize health and social services to strengthen individual and collective social and emotional wellbeing.Results: Eighty-three participants contributed to interviews and yarning circles including 17 Aboriginal community members, 38 Aboriginal and Torres Strait Islander service providers, and 28 non-Indigenous service providers. They expressed the need for codesigned, strengths-based, accessible and flexible services delivered by Aboriginal and Torres Strait Islander workers with lived experience employed in organisations with Aboriginal and Torres Strait Islander leadership and governance. Community hubs and cultural events in addition to one-stop-shop service centres and pre-crisis mental health, drug and alcohol and homelessness services were among many strategies identified.Holistic approaches to the promotion of social and emotional wellbeing are critical. Aboriginal and Torres Strait Islander people are calling for places in the community to connect and practice culture. They seek culturally safe systems that enable equitable access to and navigation of health and social services. Aboriginal and Torres Strait Islander workforce leading engagement with clients is seen to safeguard against judgement and discrimination, rebuild community trust in the service system and promote streamlined access to crucial services.